1987
DOI: 10.2136/sssaj1987.03615995005100050036x
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Conductivity of Three Southeastern Soils as Affected by Sodium, Electrolyte Concentration, and pH

Abstract: In the humid southeastern USA, little attention is given to the effect of electrolyte concentration or low levels of Na on clay dispersion, although dispersion‐related phenomenon such as surface crusting and erosion are common. Our objective was to determine the effect of electrolyte concentration, sodium absorption ratio (SAR), and soil pH on saturated hydraulic conductivity of three soils that differed in parent material. Cores packed with sieved soil at different pHs were leached with 10 pore volumes of sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 0 publications
1
15
1
Order By: Relevance
“…Suarez et al (1984) found that, at constant sodium adsorption ratio (SAR) and electrolyte concentration and at solution pHs of 6, 7, 8, and 9, hydraulic conductivity decreased and clay dispersion increased with increasing pH for two arid zone soils, one predominantly kaolinitic and one predominantly montmorillonitic. In a similar experiment on three soils from Georgia, Chiang et aL (1987) found the hydraulic conductivity of one soil to be sensitive and that of two others to be nonsensitive to pH changes from 4.5 to 8.5. They did not relate these differences to clay mineralogy.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Suarez et al (1984) found that, at constant sodium adsorption ratio (SAR) and electrolyte concentration and at solution pHs of 6, 7, 8, and 9, hydraulic conductivity decreased and clay dispersion increased with increasing pH for two arid zone soils, one predominantly kaolinitic and one predominantly montmorillonitic. In a similar experiment on three soils from Georgia, Chiang et aL (1987) found the hydraulic conductivity of one soil to be sensitive and that of two others to be nonsensitive to pH changes from 4.5 to 8.5. They did not relate these differences to clay mineralogy.…”
Section: Introductionmentioning
confidence: 94%
“…hydraulic conductivity (Suarez et al, 1984;Chiang et al, 1987) and clay dispersion of soils (Suarez et aL, 1984;Gupta et al, 1984). Suarez et al (1984) found that, at constant sodium adsorption ratio (SAR) and electrolyte concentration and at solution pHs of 6, 7, 8, and 9, hydraulic conductivity decreased and clay dispersion increased with increasing pH for two arid zone soils, one predominantly kaolinitic and one predominantly montmorillonitic.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated SAR values ( >13.0 mmol 1/2 L -1/2 ) do not cause physical degradation of soil if the system also contains high levels of soluble salts (Quirk and Schofield, 1955;McNeal et al, 1968;Frenkel et al, 1978;Shainberg et al, 1981;Abu-Sharar et al, 1987;Chiang et al, 1987;Lima et al, 1990;Malik et al, 1992;Curtin et al, 1994;Mace and Amrhein, 2001;Quirk, 2001). Conversely, physical degradation has been observed in soils with SAR levels below 13.0 mmol 1/2 L -1/2 when combined with low EC (Sumner, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies on the effects of solution pH on miscible displacement experiment for exchanging ions have been reported (Chan et al 1978(Chan et al , 1980aNielsen et al 1986;Ishiguro et al 1992). Studies on permeability change influenced by pH have also been few (Suarez et al 1984;Chiang et al 1987;Nakagawa and Ishiguro 1994;Ishiguro et al 2001). Allophanic Andisols, typical volcanic ash soils, have much amount of pH dependent charge (Okamura and Wada 1983;Iimura 1966).…”
mentioning
confidence: 99%